2020
DOI: 10.1159/000511849
|View full text |Cite
|
Sign up to set email alerts
|

Unifocal versus Multiple Ileal Neuroendocrine Tumors Location: An Embryological Origin

Abstract: <b><i>Introduction:</i></b> Small-intestinal neuroendocrine tumors (SI-NET) are situated preferentially within the ileum. The aim was to describe a potential difference in location between unifocal and multiple ileal-NET. <b><i>Patients and Methods:</i></b> Between December 2010 and December 2019, all consecutive patients who underwent resection in our European Neuroendocrine Tumor Society Center of Excellence, of at least 1 non-duodenal SI-NET, were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…All patients with localised SBNET with or without mesenteric lymph node metastases, and those with resectable liver metastases should be considered for surgery with an intent to eliminate macroscopic disease [ 9 ]. Meticulous abdominal exploration and palpation of the entire small intestine are pivotal since preoperative imaging understages the disease in up to 70% of cases [ 3 , 10 ] and in up to 50%, multiple primaries can be found [ 11 ]. Resection of primary tumour/s follows the principles of intestinal sparing surgery by avoiding extensive en-bloc resections, preserving the proximal portion of the superior mesenteric artery and vein, and thus minimizing the risk of postoperative short bowel syndrome [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…All patients with localised SBNET with or without mesenteric lymph node metastases, and those with resectable liver metastases should be considered for surgery with an intent to eliminate macroscopic disease [ 9 ]. Meticulous abdominal exploration and palpation of the entire small intestine are pivotal since preoperative imaging understages the disease in up to 70% of cases [ 3 , 10 ] and in up to 50%, multiple primaries can be found [ 11 ]. Resection of primary tumour/s follows the principles of intestinal sparing surgery by avoiding extensive en-bloc resections, preserving the proximal portion of the superior mesenteric artery and vein, and thus minimizing the risk of postoperative short bowel syndrome [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Netrin-3 could represent a therapeutic vulnerability for SCLC. Much work remains to be done to understand the molecular mechanisms and clinical implications of axonal guidance factors in cancer and resistance to treatment via cell death blockade in particular in neuroendocrine tumors [ 70 , 71 ].…”
Section: Team Workmentioning
confidence: 99%
“…The majority of SiNETs are low grade well-differentiated tumors, usually diagnosed at advanced stages and often present with metastases and stage IV tumor, highlighting their high metastatic potential [3]. Interestingly, SiNETs are often multifocal, with a common finding of synchronous multiple primaries along the small intestine [4,5]. Two recent studies demonstrated that synchronous SiNETs primaries within the same individual usually do not share somatic alterations, indicating that they arise from different cell clones [6,7].…”
Section: Introductionmentioning
confidence: 99%